Penerapan Strategi Konsumen Sentris dalam Perekonomian terhadap Kesejahteraan Konsumen - Yusuf, Satria Bagus; Karen Rehulina Ananda Ariawan, Ni Kadek; Darodjat, Rafan (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Consumers are regarded as kings, playing a pivotal role in the advancement of any business; without consumers, producers would be unable to generate profit. The world economy has developed and undergone many changes. There has been a paradigm shift from a product-centric approach to a consumer-centric one, aligning with the notion that “the consumer is king,” wherein business actors adopt approaches that prioritize consumers by addressing their needs and welfare—key determinants of business success. The consumer-centric strategy embodies the principles enshrined in Law No. 8 of 1999 on Consumer Protection. This study aims to explain the impact of implementing a consumer-centric strategy within the economy on business actors in Cileunyi Kulon through Community Service (Pengabdian Pada Masyarakat, PPM) activities. The service method employed involved initial legal research, followed by Participatory Action Research (PAR), engaging local entrepreneurs in active participation. The research team then optimized outcomes through mentoring activities. This PPM initiative resulted in a significant improvement in business actors’ understanding of consumer-centric strategies and their implications for consumer welfare.